Peran Ditpolairud Polda Bali dalam Pelaksanaan Patroli Laut Guna Mencegah Terjadinya Tindak Pidana di Wilayah Perairan Provinsi Bali - I Gede Danu Dirta Darmawan; Kadek Apriliani (Jurnal Hukum Mahasiswa, 2026)
This study aims to understand and analyze the role of the Bali Regional Police Water and Air Directorate (Ditpolairud Polda Bali) in conducting maritime patrols to prevent criminal acts in the waters of Bali Province, as well as to identify the obstacles encountered in carrying out these duties. This study employs a sociological approach, which is then analyzed qualitatively using a descriptive-analytical method. The results indicate that Ditpolairud Polda Bali plays a strategic role in maintaining the security of the waters through regular maritime patrols and the development of coastal communities. However, the implementation of patrols still faces several challenges, including limited facilities and infrastructure, personnel shortages, and unpredictable weather and geographical conditions. The conclusion of this study is that the role of the Bali Police Marine and Air Directorate in conducting sea patrols has been running quite well and contributes to efforts to prevent criminal acts in the waters of Bali Province. Nonetheless, there is a need to improve capacity, both in terms of facilities and infrastructure, the quality of human resources, and inter-agency coordination so that task implementation can run more optimally in the future.